KEMAMPUAN MENULIS TEKS NEGOSIASI SISWA KELAS X SMK NEGERI 5 PEKANBARU - Yorie Aprilliani; Nursal Hakim; Dudung Burhanudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study provided the opportunity to write the text of the negotiation of students from class X of SMK Negeri 5 Pekanbaru. This study is aimed at finding and describing the ability to write the text of the class X student association of SMKN 5 Pekanbaru and the considerable difference in writing skills of negotiation text from class X students of SMK Negeri 5 Pekanbaru is stylish or a group. The method used is the inferential quantitative method. The data from this research is the result of the possibility to write the text of the negotiation text of class X students of SMK Negeri 5 Pekanbaru, consisting of 14 classes with a total of 365 students and the number of sample 191 students. Based on the research, the result obtained was that (1) the ability to write the text of negotiation of class X students from SMK Negeri 5 Pekanbaru is moderate; (2) the possibility to write the text of the negotiation of class X students of SMK Negeri 5 Pekanbaru between different classes, its meaning, there is a difference in writing skills of negotiation text of class X students of SMK Negeri 5 Pekanbaru between colleagues class X or some class X. Overall, the ability to write the text of the negotiation of students of Class X SMK Negeri 5 Pekanbaru moderate category that is on average 68.59 worth. Moreover, there are considerable differences in the ability to write the text of the negotiation of students from class X of SMK Negeri 5 Pekanbaru.Keywords: Writing, negotiation text, class X student of SMK Negeri 5 Pekanbaru